Nutritional Ketosis with Ketogenic Diets or Exogenous Ketones: Features, Convergence, and Divergence. Issue 7 (July 2020) - Poff, Angela M.; Koutnik, Andrew P.; Egan, Brendan
Abstract : Abstract: Athletes, clinicians, and practitioners are increasingly interested in the proposed performance and therapeutic benefits of nutritional ketosis (NK). NK is best operationally defined as a nutritionally induced metabolic state resulting in blood β-hydroxybutyrate concentrations of ≥0.5 mM. Most tissues readily metabolize ketone bodies (KBs), and KBs in turn regulate metabolism and signaling in both a systemic and tissue-specific manner. During fasting, starvation, or ketogenic diets, endogenous synthesis of KBs is amplified resulting in a state of NK. Orally administered exogenous ketone supplements rapidly elevate circulating KBs and produce a similar, but far from identical, metabolic state. NK results in a number of convergent features regardless of endogenous or exogenous induction; however, important differences also are observed. The implications of NK across health, disease, and performance is rapidly becoming more evident, thus acknowledging the convergent and divergent features of NK is critical for fully understanding the potential utility of this metabolic state. Abstract : Ketogenic diets and exogenous ketones have similarities but also key differences with implications for performance and therapeutics.